Omega-3 Fatty Acids Improve Functionality of High-Density Lipoprotein in Individuals With High Cardiovascular Risk: A Randomized, Parallel, Controlled and Double-Blind Clinical Trial - Cartolano, Flávia De Conti; Dias, Gabriela Duarte; Miyamoto, Sayuri; Damasceno, Nágila Raquel Teixeira (Frontiers in Nutrition, 2022)
Omega-3 (ω 3) fatty acids have been extensively studied for primary and secondary prevention of cardiovascular health, but their ability to modulate HDL functionality remains unclear. The purpose of this study was to investigate the role of ω 3, rich in eicosapentaenoic (EPA) and docosahexaenoic (DHA), on HDL functionality. For that, 147 individuals with high cardiovascular risk were randomized in ω 3 (1 g of fish oil each - 370 mg of EPA and 230 mg of DHA, 3 times per day total EPA+DHA = 1,800 mg) or ω 6groups (1 g of sunflower oil each - 760 mg of linoleic acid, 3 times per day; total linoleic acid = 2,280 mg). Fasting blood samples were collected at baseline time and after 8 weeks of follow-up and, and the lipid profile and glucose metabolism were evaluated from plasma. From HDL, the fatty acid profile, apolipoproteins (Apo AI, CII and CIII), paraoxonase-1 (PON1), cholesteryl ester transfer protein (CETP), subfractions and antioxidant activity were investigated. Omega-3 improved large HDL (HDL=28.7%) and reduced small HDL (HDL10=-10.6%) and the non-esterified fatty acids in HDL (NEFAs-HDL) level (-16.2%). A significant reduction in CETP activity was observed in the ω 3group (Δ ω 6=3.60 pmol/ul/h and Δ ω 3= 1.99 pmol/ul/h; p=0.044). The antioxidant capacity estimated by Lag time analysis did not change after the ω 3intervention. Changes in PON1 and Apo AI were inversely associated with increased incorporation of EPA (AOR=0.446; IC=0.200-0.994) and DHA (AOR=0.351; IC=0.150-0.821) in HDL, respectively. Cardioprotective profile obtained by pooled fatty acids analysis was related to a decrease in Apo CIII (r=-0.638; p=0.002) and CETP (r=-0.341; p=0.012) and an increase in Apo CII (r=0.448; p=0.042) and PON1 (r=0.388; p=0.003). In conclusion, omega-3 was effective in the reduction of cardiovascular risk associated with HDL functionality by size improvement and changes in its lipid, antioxidant and enzyme composition.